'I was so done in that I just recognized it very plainly, "You need to do something"': Men's narratives of struggle, distress and turning to meditation. (March 2013) - Lomas, Tim; Cartwright, Tina; Edginton, Trudi; Ridge, Damien
Traditional masculinities can mean men are unable or unwilling to deal constructively with distress. However, researchers increasingly acknowledge that men and masculinities (including hegemonic styles) are diverse. Moreover, men can positively manage their well-being, although little research explores how they do so. Uniquely, our study sought to find men who report finding ways to care for themselves to examine narratives about how such self-care originated. We aimed to do this by exploring issues underpinning men's journeys towards meditation, focusing on implications for well-being. In-depth interviews were conducted in 2009 with 30 meditators, selected using principles of maximum variation sampling, and analysed with a modified 'constant comparison' approach. Men's journeys towards meditation were fraught with difficulties. Men described crossing a threshold from boyhood into 'manhood' where they encountered traditional forms of masculinity (e.g. stoicism), and most described subsequent strategies to disconnect from emotions. While men eventually found ways to engage more constructively with their emotions and well-being, this article explores the struggle and distress of their journeys.